Building Organic Bridges: Volume 2, Germany - India - Gerold Rahmann; Uygun Aksoy (Johann Heinrich von Thünen-Institut, 2014)
[Foreword ...] The 18th IFOAM Organic World Congress held on 13-15 October, 2014 in Istanbul-Turkey targets to 'build organic bridges'. The Scientific track will contribute to bridging not only scientists but also institutions and disciplines, and to linking more developed and less developed, rural and urban, research to extension, plant to animal, farm practices to world-wide problems and producer and consumers. Organic is a management system that requires a diversity of inputs from different disciplines, therefore, an international Congress is the best medium to blend them. The Scientific Track is organized with special efforts of the co-organizers, International Society for Organic farming Research (ISOFAR; www.isofar.org) and EGE University (Turkey; www.ege.edu.tr). Organic e-prints (www.orgprints.org) acted as the hub for collection, revision and maintaining of all the papers. There were 568 manuscripts and abstracts received for the Scientific Track. Abstracts were not evaluated since the authors were obliged to submit full papers. About 96 reviewers - 37 from Turkey and 59 from all over the world (ISOFAR network) - contributed to the review process (double-blind: 1 reviewer international, 1 reviewer Turkish, final assessment and decision by the scientific board). At least, 300 papers have been accepted. They are from 51 countries and represent the countries, were 87 % of the global organic farm land and 75 % of the global organic farms are located. It is obvious, that organic farming is practiced world wide (but less the 1 % of the total farm land is managed organically), the organic markets are mainly in the western world (Europe, North America, Japan: 94 %) and the research is mainly done in Europe (publication share in web of science: 84 %, at the 4th ISOFAR congress: 69 %). [...] The papers are ordered by countries (country of the first author), not by sessions or disciplines. These decisions are made to make the proceedings affordable (all volumes can be purchased individually) and to merge and bridge the world and not split by disciplines and sessions. You find search facilities (indexes) to find all papers by discipline, eprint-number, keywords or sessions in each volume. A download of the full proceeding is possible under the webpage of ISOFAR (www.isofar.org) and as individual papers under organic eprints (www.orgprints.org). Due to the fact that all papers together comprise 1,300 pages, the printed Proceedings are split into four volumes. These proceedings comply all submitted, accepted for oral or poster presentation and revised manuscripts, but does not imply that they are all presented. The content of the papers are in responsibility of the authors and do not need to comply with the editors opinion.
urn:nbn:de:gbv:253-201407-dn053622-7; Additional information: Proceedings of the 4th ISOFAR Scientific Conference at the Organic World Congress 2014, 13-15 October 2014 in Istanbul, Turkey.
Keywords: 630